Development of Wound Dressing Hydrogel Based Combination of κ-Carrageenan and Chitosan - Rizki Fadila, Alma; Zai, Khadijah (Iranian Journal of Pharmaceutical Sciences, 2024)
Wound dressing has an essential role in the wound-healing process because it can help accelerate wound healing and prevent infection. One of the wound dressings that needs to be developed is a hydrogel-based wound dressing because hydrogel can retain moisture and absorb accumulated fluid on the wound. Moreover, hydrogel can also be used as a matrix for therapeutic agent delivery. Therefore, this study aimed to develop a hydrogel film-based wound dressing using a combination of κ-carrageenan and chitosan. The optimum formula was determined based on the simplex lattice design. The parameters for optimization included swelling ratio, water vapor transmission rate (WVTR), and film degradation ratio. The optimum hydrogel film formula had a concentration of 1.5% κ-carrageenan and 0.5% chitosan. It exhibited a swelling ratio of 423.68 ± 60.52%, a WVTR of 831.54 ± 63.36 mg/cm2.day, a pH of 5.2 ± 0.27, a tensile strength of 0.0681 ± 0.009 mPa, and a hydrogel film degradation of 66.64 ± 20.96% after three days. These results suggest that the optimum hydrogel film-based combination of κ-carrageenan and chitosan is a promising alternative wound dressing.